KECERDASAN EMOSI DAN STRES KERJA PADA PERAWAT DI RUMAH SAKIT SOERADJI TIRTONEGORO - Maria Kaptenia Mayrere; Sutarto Wijono (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2025)
This study aims to examine the relationship between emotional intelligence and job stress among nurses at Rumah Sakit Soeradji Tirtonegoro (RSST). The background of this research is based on the high emotional pressure and workload, both administrative and in direct patient care, that nurses often face. This study employed a quantitative approach with a correlational method. A total of 52 nurses were selected as the sample using a saturated sampling technique. Data were collected using the Emotional Intelligence Scale and the Job Stress Scale, and analyzed using Pearson correlation. The results showed a significant negative relationship between emotional intelligence and job stress, with a correlation coefficient of r = -0.574; p < 0.05. The higher the nurses’ emotional intelligence, the lower their level of job stress. These findings highlight the importance of emotional intelligence as a protective factor against work-related stress and support the enhancement of service quality. The study recommends implementing emotional intelligence training for nurses to reduce job stress and improve psychological well-being in hospital settings.